Unforgettable Days (Reminiscences recorded by Huu Mai): Third Edition - Võ, Nguyên Giáp (Thế giới, 2014)
From August 1945 to December 1946, from the victory of the General Insurrection (known as the 1945 revolution) to the start of the resistance to French colonial aggression, Vietnam went through a crucial period, one that was extremely complex and at times critical.